THE STRATEGIES OF ENGLISH LANGUAGE TEACHING AT IAIN BONE - Ishak, Ishak; Nahdhiyah, Nahdhiyah (English Language Teaching for EFL Learners Journal, 2020)
This research aims at investigating the strategies of English language teaching at IAIN Bone. The data were collected through structured interview. The strategy aims to improve language skill, improve knowledge, reaching goals and encourage motivation. It is to promote critical, reflective thinking and evaluation skills that will help students to take positive action to protect, enhance and advocate for their learning. Lecturers use communicative personal and pedagogical capability to work collaboratively with their students in learning activities. The lecturers are hoped to bring and involve the students into a quality of better education. The research is synthesized into top five teaching strategies: apply method based on the material, have clear instruction and method, lead the students to the greater understanding, have adequate knowledge about their individual students, and build a good rapport with students.